Kingdom of bones : a thriller - Rollins, James, 1961- (Rollins, James, 1961- Sigma Force novel, 2022)
It begins in Africa ... A United Nations relief team in a small village in the Congo makes an alarming discovery. An unknown force is leveling the evolutionary playing field. Men, women, and children have been reduced to a dull, catatonic state. The environment surrounding them--plants and animals--has grown more cunning and predatory, evolving at an exponential pace. The insidious phenomenon is spreading from a cursed site in the jungle -- known to locals as the Kingdom of Bones --and sweeping across Africa, threatening the rest of the world. What has made the biosphere run amok? Is it a natural event? Or more terrifyingly, did someone engineer it? Commander Gray Pierce and Sigma Force are prepared for the extraordinary and have kept the world safe, vigilance for which they have paid a tragic personal price. Yet, even these brilliant and seasoned scientific warriors do not understand what is behind this frightening development--or know how to stop it. As they race to find answers, the members of Sigma quickly realize they have become the prey. To head off global catastrophe, Sigma Force must risk their lives to uncover the shattering secret at the heart of the African continent--a truth that will illuminate who we are as a species and where we may be headed... sooner than we know. Mother Nature--red in tooth and claw--is turning against humankind, propelling the entire world into the Kingdom of Bones.